Natural Radioactivity Levels in Tap and Bottled Water Samples for Some Primary Schools of Karbala Governorate, Iraq - J. Musa , Hayder; J. Najim , Adil; J. Al-Saadi , Abbas (Pure Sciences International Journal of Kerbala, 2025)
Natural radioactivity levels of 226Ra, 232Th, and 40K were assessed in 10 tap water samples collected from different schools in Karbala govenorate, as well as 5 commercial bottled drinking water samples. The activity concentrations were measured using gamma spectrometry with a NaI(Tl) 3"×3" detector equipped with a specially designed shield. In tap water samples, the activity concentrations of 226Ra, 232Th, and 40K ranged from <0.063 to 0.817, <0.067 to 0.493, and <0.117 to 9.896 Bq·L⁻¹, respectively. For bottled water, 226Ra and 232Th concentrations were below the Minimum Detectable Actictivity (MDA), while 40K ranged from <0.117 to 8.180 Bq·L⁻¹. Overall, tap water samples exhibited higher concentrations than bottled water. The measured values for tap water were within the ranges reported in the literature for other countries. Health implications were estimated by calculating the annual effective dose received by school-age children due to ingestion of radionuclides. The average values of annual effective dose in tap and bottled water were 85.05 and 36.40 μSv·y-1 respectively. All calculated doses were below the global mean level of 100 μSv·y-1, as reported by World Health Organization (WHO). It is therefore concluded that both tap water and bottled water consumed in schools of Karbala Governorate are radiologically safe and pose no significant health hazard to the public.